2009
DOI: 10.1111/j.1471-4159.2009.06325.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying glutamatergic dysfunction in schizophrenia: therapeutic implications

Abstract: Early models for the etiology of schizophrenia focused on dopamine neurotransmission because of the powerful antipsychotic action of dopamine antagonists. Nevertheless, recent evidence increasingly supports a primarily glutamatergic dysfunction in this condition, where dopaminergic disbalance is a secondary effect. A current model for the pathophysiology of schizophrenia involves a dysfunctional mechanism by which the NMDA receptor (NMDAR) hypofunction leads to a dysregulation of GABA fast-spiking interneurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 122 publications
(235 reference statements)
5
48
0
3
Order By: Relevance
“…At present, several therapeutic strategies in schizophrenia involve the glutamatergic system (Gaspar et al 2009), for instance, addressing the glycine site of the NMDA-R (Millan 2005;Shim et al 2008) or metabotrobic glutamate receptors (Patil et al 2007). These mechanisms might be a mode to also alleviate the affective and cognitive deficits of schizophrenia (Krystal et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, several therapeutic strategies in schizophrenia involve the glutamatergic system (Gaspar et al 2009), for instance, addressing the glycine site of the NMDA-R (Millan 2005;Shim et al 2008) or metabotrobic glutamate receptors (Patil et al 2007). These mechanisms might be a mode to also alleviate the affective and cognitive deficits of schizophrenia (Krystal et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Human postmortem studies with brain samples of schizophrenic patients revealed reduced NMDA-R subunit expression as well as less NMDA binding sites (Ibrahim et al 2000), altered NR1 expression (Vrajova et al 2010), lower numbers of parvalbumin-positive GABAergic interneurons expressing NR2A (Bitanihirwe et al 2009), and reduced expression of the NMDA-R-associated protein PSD95 (Funk et al 2009). Since NMDA-R-dependent activity of parvalbumin-positive GABAergic interneurons markedly influences the electrophysiological functions of the prefrontal cortex, NMDA-R hypofunction disturbs the proper representation of "noise" and "signal to noise" relations (Belforte et al 2010;Gaspar et al 2009;Gonzalez-Burgos and Lewis 2008;Gordon 2010;Homayoun and Moghaddam 2007;Rolls et al 2008;Roopun et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The hypofunction of glutamatergic receptors is the pathophysiology of schizophrenia of the glutamatergic hypothesis, and the N-methyl-d-aspartate receptor (NMDAR) antagonists, such as dizocilpine (MK-801), phencyclidine, and ketamine, produce schizophrenia-like behavior and cognitive deficits (Gaspar, Bustamante, Silva, & Aboitiz, 2009;Lobellova et al, 2013;Meltzer et al, 2013). Acute treatment with MK-801 is extensively utilized to establish animal model of cognitive impairment, such as spatial learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…NMDAR antagonists reproduce both the positive and negative symptoms of schizophrenia in humans and worsen the symptoms of nonmedicated patients (Gaspar et al, 2009), suggesting that NMDAR hypofunction contributes to the symptoms of schizophrenia. Consistent with this hypothesis, enhancing NMDAR function by administering agonists acting at the NMDAR glycine site has been reported to be effective in reducing symptoms of schizophrenia (Labrie and Roder, 2010).…”
Section: Introductionmentioning
confidence: 99%